AB0240 The Effect of Anti Estrogen Therapy (AET) on Rheumatoid Arthritis. (9th June 2015) - Alhaddad, B.; Ballou, S.; Chen, J.
Abstract : Background: The musculoskeletal side effects of anti-estrogen therapy, especially Aromatase Inhibitors (AI), are now well established and the name AIA (Aromatase inhibitors induced arthralgia) has been proposed to describe actual inflammatory arthritis related to these medications (1). Recent observations by our group suggest increased incidence of RA among patients using either AI or selective estrogen receptor modulators (SERMs) (2) Objectives: We intended to examine any effect of AET on disease activity in patients with established RA Methods: We searched the electronic medical records in our facility using ICD-9 codes for all patients with the diagnoses of both breast cancer and Rheumatoid arthritis. We reviewed charts to isolate those with validated RA diagnosis who have used Tamoxifen or AI for breast cancer. The primary outcome measure was worsening of disease within 1-18 months after starting AET based on one or more of the following: Increased tender or swollen joint counts, addition of new DMARDs, withdrawal of AET because of worsening pain/swelling, and new onset RA. The worsening could not be attributed to changes or discontinuation of RA therapy. All data were extracted from Rheumatology clinic notes within 1-12 months of starting AET. Laboratory markers for inflammation were not considered because they were thought to be influenced by recent cancer diagnosis Results: Fifteen patients were included in this analysis. Mean age was 59 years and median duration of RA prior to cancer diagnosis was 7.1 years. Old age and lung cancer were the cause of death in the 2 patients who expired. All patients but one had ductal carcinoma ( in citu or infliltrative) with negative HER2 amplification. AET used included Tamoxifen (4), Anastrazole (10) and Lotreziole (1). Most patients were on stable DMARDs. One patient only was on biologic (abatacept) which was continued with no worseneing of her RA after AET initiation. Nine of 13 with available serology were seropositive; 2 of them developed new onset RA within a year of starting. RA worsened in 8 patients (54%) after initiating AET: 2 had new onset disease, 1 with flaring after years of remission, 1 had to stop AET (Anastrazole), 2 had to add/increase DMARDs and 2 had increased number of swollen/tender joints on expert assessment. One of the patients who used tamoxifen developed new onset RA starting with knees involvement while the other 3 did not have worsening of their established RA. With the use of AIs; 63% had worsening including 1 new onset RA with anastrasole. Among those who worsened, symptoms started within 2-5 months in most patient except 1 with later worsening (18 months later). On comparing patients who worsened to those who did not; patients with worsening tended to be younger (57 vs. 61: P=0.55) and had longer duration of disease (8.4 vs. 5.6 years P=0.5). Conclusions: Our data suggest that use of AET may worsen disease activity in patients with rheumatoid arthritis as well as increasing the incidence of the disease. Young age and long disease duration for RA increased the trend for worsening. Our study is limited by the small number of patients References: Niravath P. Aromatase inhibitor-induced arthralgia: a review. Ann Oncol. 2013 Jun;24(6):1443-9 Chen JY, Ballou SP. The Effect of Antiestrogen Agents on Risk of Autoimmune Disorders in Patients with Breast Cancer. J Rheumatol. 2014 Oct 1. Disclosure of Interest: None declared